2011
DOI: 10.1002/jso.22066
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐142‐3p as a potential prognostic biomarker for esophageal squamous cell carcinoma

Abstract: The main findings suggest that miR-142-3p is involved in the progression of ESCC and is a potential prognostic biomarker for ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 44 publications
1
79
2
Order By: Relevance
“…Recent studies have found that miRNA has the effects of both oncogenes and anti-oncogenes and plays an important role in the initiation and development of tumors (Zhou et al, 2009;He et al, 2012). Numerous miRNAs directly participate in the initiation and development of tumors, and miRNA spectra are correlated with the diagnosis, staging, progression, and prognosis of EC (Lin et al, 2012;Xu et al, 2012;Yang et al, 2013). Studies using microarray technology on the miRNA expression spectra of 31 EC tissue samples have discovered that 46 miRNAs exhibit abnormal expression, 7 of which exhibit significant differences, compared with those in normal tissues; furthermore, the high expression of has-miR-103/107 is closely correlated with low survival rate.…”
Section: Screening Of Microrna In Patients With Esophageal Cancer At mentioning
confidence: 99%
“…Recent studies have found that miRNA has the effects of both oncogenes and anti-oncogenes and plays an important role in the initiation and development of tumors (Zhou et al, 2009;He et al, 2012). Numerous miRNAs directly participate in the initiation and development of tumors, and miRNA spectra are correlated with the diagnosis, staging, progression, and prognosis of EC (Lin et al, 2012;Xu et al, 2012;Yang et al, 2013). Studies using microarray technology on the miRNA expression spectra of 31 EC tissue samples have discovered that 46 miRNAs exhibit abnormal expression, 7 of which exhibit significant differences, compared with those in normal tissues; furthermore, the high expression of has-miR-103/107 is closely correlated with low survival rate.…”
Section: Screening Of Microrna In Patients With Esophageal Cancer At mentioning
confidence: 99%
“…It was suggested that miR-142 may play an important role in maintaining the selfrenewal capacity of bronchioalveolar stem cells (7). It was also found that esophageal squamous cell carcinoma patients with high expression of miR-142 had poorer survival rates than those with low expression of miR-142, suggesting that miR-142 may act as a tumor suppressor (8). miR-142 was found to be downregulated in osteosarcoma cell lines (9), however, the role of miR-142 in osteosarcoma remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that miR-142 may play an important role in maintaining the self-renewal capacity of bronchioalveolar stem cells (15). It was also reported that patients with esophageal squamous cell carcinoma (ESCC) displaying a high expression of miR-142 had poorer survival rates compared with those with low expression of miR-142, suggesting that miR-142 may act as a tumor suppressor (16).…”
Section: Introductionmentioning
confidence: 99%